Larangan Pembebanan Merchant Discount Rate QRIS Kepada Konsumen dalam Perspektif Hukum Ekonomi Digital - JAE WOO KO (Jurnal Hukum Lex Generalis, 2026)
The development of QRIS as a digital payment instrument provides convenience for consumers and merchants. However, some merchants still charge Merchant Discount Rate or QRIS administration fees to consumers. This study examines MDR regulation, the phenomenon of additional QRIS charges and its legal implications from the perspective of digital economic law. This research uses a normative juridical method with statutory, conceptual and limited comparative approaches. The study concludes that charging MDR to consumers is inconsistent with price transparency, consumer protection and legal certainty in digital payment systems.